The Place of Morality in the Nigerian Educational System - Olaniyi, A. J.; Oyelade, A. F. (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
This paper analyses the place of morality in the Nigerian educational system. This is necessary because of the declining moral values in the Nigerian society as evident in the frequency of immoral activities like fraud, sexual immorality, forgery, bribery and corruption. Unfortunately, immoral activities have adversely affected the Nigerian educational system. Thus this paper is interested in examining the place of morality in the Nigerian educational system. The method of research employed in the paper is the method of philosophical analysis. This is because the paper is a philosophical research. It therefore uses philosophical analysis which includes logical, linguistic, expository, and critical analyses. All these are to help in the clarification of the ideas in the study for better understanding of the issues and arrival at sound conclusions. It was found that moral education features in the Nigerian educational system. However, it features impressively only at the policy level, in the National Policy on Education. At the practice level, moral education does not feature impressively at the various levels of the educational system. However, the fault is traced to the unimpressive manifestation of moral rectitude in the larger society. This does not provide enabling environment for sound moral education in the schools. It is therefore recommended that, the leaders of thought in the larger society; politicians, parents, religious leaders, and so forth, should give better leadership to the society and the schools through demonstration of sound moral practices – this would provide enabling environment for the teaching of good moral education in the schools. Keywords: Morality, moral education, National Policy on Education, principles of good moral behaviour, philosophical analysis.